Minerals In The World Economy - Charles L. Kimbell (The National Institute for Occupational Safety and Health (NIOSH), 1981)
The year 1979 was a period of increased activity for the world's mineral industry, distinctly in contrast with 1978 when estimated world crude mineral output value declined slightly and most phases of the industry's activity were somewhat curtailed. In 1979, most major mineral commodities recorded significant gains in output, with a substantial number achieving new record highs; details on trade levels for 1979 were not available, but increases over those of 1978 were expected on the basis of partial data. Consumption of most commodities edged higher; in some cases the higher demand levels were met largely through draw-downs of stocks accumulated in recent years, while in other cases notable output increases were required to meet demand. Actually, 1978 was not a bad year for all elements of the mineral industry if changes in output levels of the various commodities are considered as a measure of performance. There were far more individual commodities registering production increases between 1977 and 1978 than registered declines, but some of those reported as declining were relatively major commodities (bauxite, aluminum, copper and zinc were notable), Moreover, the upturn in productive activity in 1978 was not matched by increases in profits. However, 1979 was unquestionably a year of renewed expansion efforts, although some commodity areas, most notably the steel industry component, were still experiencing difficulties.